An improved extraction method for surface dosage of insecticides on treated textile fabrics. (December 2017) - Dieval, Florence; Bouyer, Jérémy; Fafet, Jean-François
Abstract Background Tens of millions of people live in mosquito-infested regions and controlling mosquito-borne diseases is one of the major interventions aimed at alleviating poverty worldwide. The use of insecticide-treated textiles is one of the most widespread control measures. This includes bed nets, battle clothing or, more generally, textiles use for clothing. These textiles are generally treated with permethrin as active ingredient, which is dosed after extraction of the active molecule present throughout the fabric (measured in mg permethrin/g of fabric) and does not take the effective concentration on the textile surfaces into account. The objective of this study was to propose an improved dosage method that enables measurement of the bioavailable or effective part of active ingredients on the surface of textile treated with insecticides. Methods The proposed method relies on mechanical extraction of active molecules on the surface of the textile in direct contact with either the skin or with the targeted arthropod. Results The results showed that the amount of permethrin measured using the current method is about 200 times higher than the effective surface concentration of the insecticide. In addition, the type of weave or knit influences the effective concentrations of permethrin on the surface of the textile. With the current dosage method, the variation in the concentration of permethrin depending on the type of weave is maximum 8%, whereas with the proposed method, it varies by about 50%. These results were confirmed by bioassays, in which the type of weave significantly affected (p < 10−3 ) the 100% knockdown time ofAnopheles gambiae . Conclusions The bioefficacy of insecticide treatments of fabrics is directly correlated with the effective concentration of insecticide on the textile surface, which can be quantified using the method proposed. This improved method could be used to redefine the limits of actual concentrations of active substance after assessment of the bioefficacy of the treatment and the risk to human health. Further, it enables assessments of the kinetics of insecticide migration in the case of long-lasting insecticide treatment.